Finite element analysis of laminated glass - Watson, Chris (Cranfield University, 2009)
In the road and rail industries, annealed float glass is combined with a thin polymeric layer to form a 3-ply glass/PVB/glass structure known as laminated glass. Amongst other characteristics, the PVB acts to retain fractured glass fragments, thus minimising injury from flying glass shards. Previous attempts at predicting the behaviour of laminated glass during impact have proven difficult due to complex stress fields caused by the large differences in moduli. The following research made an attempt at modelling laminated glass using the Laminated Glass model of LS-DYNA (MAT_32). Experimental results, used for model validation, displayed a large amount of scatter that may have been due to differences in manufacturing conditions. Numerical prediction results showed the model to be highly sensitive to mesh refinement. The resultant data showed poor correlation with experimental results predicting a much softer response.
Keywords: Laminated Glass; Finite Element; Impact; LS-DYNA; MAT_32; Polyvinyl Butyral (PVB)